2000
DOI: 10.1007/pl00008208
|View full text |Cite
|
Sign up to set email alerts
|

Increased in situ expression of nitric oxide synthase in human colorectal cancer

Abstract: There is growing evidence that nitric oxide (NO) has an important role in tumor growth. However, information on the expression of NO synthase (NOS) in colorectal cancers is scanty. We therefore investigated the distribution and expression of NOS in human colorectal cancers. The expression of three types of NOS, inducible (iNOS), endothelial (eNOS) and neuronal (nNOS), was examined by immunohistochemistry in 25 cases of colorectal cancer. The expression of iNOS was also investigated at the mRNA level using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 19 publications
3
66
1
Order By: Relevance
“…To support further the role iNOS in colon tumor promotion, mice from an Apc Min/+ -iNOS-knockout genetic background showed decreased intestinal tumor formation (Ahn and Ohshima, 2001). In humans, iNOS expression is up-regulated in carcinomas compared with patient's normal-appearing colonic mucosa (Yagihashi et al, 2000). Luteolin has an anti-inflammatory role was already reported by modulating the inflammatory mediators (Choi, 2007).…”
Section: Lefmentioning
confidence: 90%
“…To support further the role iNOS in colon tumor promotion, mice from an Apc Min/+ -iNOS-knockout genetic background showed decreased intestinal tumor formation (Ahn and Ohshima, 2001). In humans, iNOS expression is up-regulated in carcinomas compared with patient's normal-appearing colonic mucosa (Yagihashi et al, 2000). Luteolin has an anti-inflammatory role was already reported by modulating the inflammatory mediators (Choi, 2007).…”
Section: Lefmentioning
confidence: 90%
“…Recently, a large number of studies have revealed the association of iNOS expression with various cancers [35][36][37][38][39] . Yagihashi [40] studied 22 cases of colorectal cancer tissues by immunohistochemistry and RT-PCR and found increased iNOS expression was associated with colorectal cancer. Bing et al [37] found increased expression of iNOS and production of prostanoids in colorectal cancer paralleled to the increase in COX-2, confirming the importance of this emzyme in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…to upregulate their expression of NOS II and NO production (Witthoft et al, 1998). Enhanced expression of NOS II and NOS III has been recently discussed to correlate with tumour growth and vascular invasion in human colorectal cancer (Yagihashi et al, 2000;Lagares-Garcia et al, 2001). In our study the involvement of the NOS II isoform in Matrigel 1 invasion of the colorectal adenocarcinoma cell lines was evidenced by the inhibition of invasion by 1400 W, the most selective NOS II inhibitor reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main source of NO probably are tumour-associated macrophages, there are some reports that the synthesis of NO is inducible by cytokines in some human carcinoma cell lines like DLD-1, HT-29, A-172 and NIH:OVCAR-3 (Thomsen and Miles, 1998). The biological significance of NO in malignant tumours is not clear, but a recent study suggest that a high expression of NOS II and NOS III is associated with aggressive behaviour of colorectal adenocarcinomas (Yagihashi et al, 2000). The aim of the present study was to investigate if NO is able to modulate tumour cell invasiveness of human colorectal adenocarcinoma cell lines , and whether NO can be induced by cytokines produced by stromal macrophages.…”
mentioning
confidence: 93%